Complex Network of Scientific Talent Migration in Discrete Dynamics from 2001 to 2013. (16th July 2020) - Wang, Yinqiu; Luo, Hui; Shi, Yunyan
Abstract : Scientific talents can make great contributions, including scientific breakthrough innovations and discoveries, and coordinate and guide the actions of many others, propelling the scientific knowledge frontier. We investigate international scientific talent migration from 2001 to 2013 with the quantitative method. The relationship between complex network and international talent migration is introduced. Considering most of talents migrate between some countries with good economy and innovation, the migration network including 37 countries is analysed. The countries are noted by nodes of the migration network, and the migratory flow of talents from one country to another country is viewed as the directed weight edge between the corresponding nodes. The discrete dynamics of talent migration under complex network is proposed. The unknown parameters of the proposed model are identified. The overall situation and time evolution of international talent migration from 2001 to 2013 are given from the discussion on the indicators of complex network. Furthermore, we study the talent migration flows in the view of obstacle factors. It is found that the great majority of talents migrate between developed countries and emerging economies from 2001 to 2013, and this phenomenon becomes more significant. The USA has attracted a great number of talents all over the world, and the country is also the ideal destination for talents who want to live or work in another country for more job opportunities, attractive payment, and better innovation environment. China and India begin to attract talents. Talents emigrate from more and more original countries. It becomes more convenient for talents to immigrate to other countries. The effectiveness of obstructs to migration has become weakening. For immigrating to a certain country, the obstacles have a relationship with the country's innovation.